Psychologicall Well Being pada Anak Usia Dini Pasca Perceraian Orang Tuanya - Abd Azis; Luluk Alfiya (Departement of Mathematics Education, 2023)
Parents have an important role in supporting the success and success of a child, harmonious relationships in the family can influence the growth and development of children, because the family is the only place or natural environment that can educate children well and correctly, the education in question is education physical and spiritual education and can foster a sense of love and affection in their own souls, creating a peaceful family. Parents can give birth to children who have a bright future so they can be successful in the field they want. Parental divorce will have an impact on early childhood development, because they generally still need full love and attention from both parents. A broken family atmosphere can have a negative influence on mental development, because children's personalities generally occur through childhood experiences. This type of research uses observation, interviews, documentation methods and then the data can be attached and described in detail. The general results of this research are that the psychological well-being of young children after their parents' divorce is low in the dimensions of good relationships with other people and the dimension of feeling in the environment.